PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH PADA USAHA DAGANG ANAS FASHION - Desi Aulia Sari; Addiarahman; Khairiyani (EKSYA : Jurnal Ekonomi Syariah, 2022)
This research is entitled "Application of Financial Accounting Standards for Micro, Small, and Medium Entities in Anas Fashion Trading Business." The purposes of this study are (1) to determine the condition of Anas Fashion's financial statements before applying the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). (2) To find out whether the Anas Fashion Trading Business has implemented the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). While the research method used by researchers is a qualitative approach. The results of this study are: (1) The condition of the financial statements applied by the business with Anas Fashion is carried out using 2 stages of recording. The first stage is recording daily buying and selling transactions in the agenda book and the second stage is recording year-end reports in the form of operating income statements and cash flow statements. From the method of recording the financial statements, it is known that sales of Anas Fashion in the January-December 2021 period are very volatile, with the highest sales occurring in April, which amounted to Rp. 62,586,000. While the lowest sales occurred in May and June, which amounted to Rp. 18,250,000. Meanwhile, Anas Fashion's income from fashion sales is approximately 360 million per year 2021, and costs for employee salaries are 14.4 million per month, or 172.8 million per year. Meanwhile, other expenses reached 1.3 million per month or 15.6 million per year. Meanwhile, for net profit, the owner of Anas Fashion estimates the amount of profit received is around 9 million per month, or 108 million per year. (2) Anas Fashion's trading business has not yet fully implemented the MSME Standard Statement in recording financial report activities as specified in SAKEMKM. Of the 5 minimum standards set, namely profit and loss statements, statements of financial position, reports of changes in capital, cash flow statements and notes to financial statements. Anas Fashion only records 2 financial statements, namely the income statement and cash flow statement. However, in the process, Anas Fashion has carried out the journal entry stage, although it does not record the ledger. If Anas Fashion applies SAKEMKM in its financial reports, then Anas Fashion must perform two stages of recording, namely holding the recording of transactions in journals and ledgers. Then the stage of recording financial statements in the form of cash flow statements, statements of financial position, income statements, reports of changes in capital and notes to financial statements.